Current practices in missing data handling for interrupted time series studies performed on individual-level data: A scoping review in health research - Bazo-Alvarez J.C. (2021)
This study was funded by the National Institute for Health Research (NIHR) School for Primary Care Research, project number 444. JCB was sponsored by FONDECYT- CONCYTEC (grant contract number 231-2015- FONDECYT). TPM, TMP and JRC were supported by the Medical Research Council (grant numbers MC_UU_12023/ 21 and MC_UU_12023/29). The study sponsors only had a funding role in this research. Thus, the researchers worked with total independence from their sponsors.